EDUKASI MENGGOSOK GIGI TERHADAP KEMAMPUAN ANAK MENGGOSOK GIGI PADA ANAK TUNAGRAHITA DI SLB SHANTI YOGA KLATEN - Suyami Suyami; Romadhoni Tri Purnomo; Ria Sutantri (Universitas Muhammadiyah Klaten, 2019)
Mentally disabled children have a level of intelligence that is so low thatto learn developmental task requires special assistance or services, especially inthe need for education and guidance programs. Children with intellectualdisabilities in SLB Shanti Yoga Klaten still lack understanding in brushing theirteeth properly. So that mentally disabled students only brush their teeth in certainparts that only students understand. One effort to improve the ability to brushteeth against mentally retarded children is to brush their teeth.This study aimedto determine the effect of brushing teeth on children's ability to brush teeth inmentally retarded children.This type of research uses a quasi-experimental research with pre andposttest without control design. The sample in this study were mentally retardedchildren with IQ> 50. The instrument used was a tooth brushing abilityquestionnaire that was adopted and validation was tested. Bivariate statisticaltest using paired t-test.The average age of children who became respondents inthis study was 7-8 years with male gender that is 11 children. The ability to brushteeth pretest obtained an average value of 6 with a standard deviation of 2.521,while for posttest obtained a value of 8.61 with a standard deviation of 2.913, theresults of the statistical test Paired T-Test obtained the results of <alpha (0.000<0.05).There is an effect of brushing teeth on the ability of children to brush theirteeth in mentally retarded children in SLB Shanti Yoga Klaten.